Cognitive performance in childhood and early adult illness: a prospective cohort study. Issue 8 (13th July 2004) - Martin, Laurie T; Fitzmaurice, Garrett M; Kindlon, Daniel J; Buka, Stephen L
Abstract : Study objective: To evaluate whether cognitive performance in childhood is an early determinant of adult illness. Design: Prospective cohort study covering over 30 years. Setting: Providence, Rhode Island, USA. Participants: 633 people ages 30–39 followed up since birth as part of the Providence cohort of the national collaborative perinatal project. Main results: Higher cognitive performance at age 7 was related to a significantly reduced risk of serious illness in adulthood, OR = 0.65 (95%CI: 0.47 to 0.89) for a one standard deviation (15 point) increase in IQ score. This association was independent of both parental socioeconomic status and participant's attained level of education. Conclusions: General cognitive performance may be an important and informative early determinant of adult health. Further evaluation of this association and mechanisms linking cognitive performance and health may provide new and innovative strategies to improve disease management and reduce morbidity.